Relevansi Theory Z terhadap Generasi Z di Dunia Kerja Modern: Pendekatan Narrative Review [The Relevance of Theory Z to Generation Z in the Modern Workplace: A Narrative Review Approach] - Amalia, Firda Rachma; Wijaya, Jemi Cahya Adi; Mukti, Masetya (Indonesia Berdaya, 2026)
Abstract. Theory Z, introduced by William G. Ouchi (1981), is a classical management approach that emphasizes trust, loyalty, employee involvement, and well-being. However, the emergence of Generation Z with its dynamic, digital, and flexibility-oriented characteristics raises questions about the relevance of Theory Z’s values in the context of the modern workplace. This article employs a narrative review method of ten scientific articles published between 2019 and 2025 that discuss the relationship between Theory Z, employee engagement, well-being, and the characteristics of younger generations in the workplace. The findings indicate that the core values of Theory Z remain relevant but require adaptation to the psychological and social dimensions of Generation Z, such as the need for flexibility, meaningful work, and holistic well-being. New concepts such as psychological sustainability and trust-based leadership emerge as modern reinforcements of Theory Z. Abstrak. Theory Z yang diperkenalkan oleh William G. Ouchi (1981) merupakan salah satu pendekatan manajemen klasik yang menekankan kepercayaan, loyalitas, keterlibatan, dan kesejahteraan karyawan. Namun, munculnya Generasi Z dengan karakteristik yang dinamis, digital, dan menuntut fleksibilitas kerja menimbulkan pertanyaan tentang relevansi nilai-nilai Theory Z dalam konteks dunia kerja modern. Artikel ini menggunakan metode narrative review terhadap sepuluh artikel ilmiah terbitan 2019–2025 yang membahas hubungan antara Theory Z, employee engagement, well-being, dan karakteristik generasi muda di tempat kerja. Hasil kajian menunjukkan bahwa nilai-nilai dasar Theory Z masih relevan, namun perlu adaptasi terhadap dimensi psikologis dan sosial Generasi Z, seperti kebutuhan akan fleksibilitas, makna kerja, dan kesejahteraan holistik. Konsep baru seperti psychological sustainability dan trust-based leadership muncul sebagai bentuk penguatan teori Z yang modern.